Peer Education Sadari terhadap Perilaku Remaja dalam Deteksi Dini Kanker Payudara - Sitindaon, Sry Rumondang; Nasution, Siti Zahara; Nurhidayah, Rika Endah (Journal of Telenursing (JOTING), 2024)
This study aims to analyze the influence of breast self-examination peer education on adolescent behavior in early breast cancer detection. This research method is quantitative with a pre-experimental research design, one group pretest-posttest design. The sampling method in this study used proportional stratified random sampling, so the total sample in this study was 114 respondents. This research began in September 2023 – February 2024. Based on the results of statistical tests using the Wilcoxon signed rank test, the P-value was obtained, namely 0.000 < α = 0.05. In conclusion, there is an influence before and after breast self-examination peer education is carried out on adolescent behavior in early detection of breast cancer. Keywords: Adolescent Behavior, Breast Cancer, Breast Self-Examination, Peer Education